Remembering the contributions of Professors Rosa Nomen and Julià Sempere: A life devoted to chemical engineering at IQS - Serra, E.; Pou, J.O.; Berzosa, X.; Gonzalez-Olmos, R.; Borrós, S. (Process safety and environmental protection, 2023)
Professor Rosa Nomen, member of the editorial board of Process Safety and Environmental Protection, and Professor Julià Sempere both from the Institut Químic de Sarrià (IQS), Universitat Ramon Llull (Barcelona, Spain) will be retired in July 2023. They have contributed to the education of more than 1000 chemical engineers around Catalonia for 40 years. In this article, we have revisited the main scientific contributions that they have carried out in the field of chemical engineering. They had diverse research interests covering a wide range of topics in the areas of process safety and environmental protection. These included the utilization of thermal analysis and calorimetry to comprehend chemical reactions, including their safety and chemical and physical kinetics. They also focused on devising new methodologies for industrial safety and implementing flow chemistry to produce fine and specialty chemicals in a more sustainable and safer way. Additionally, they contributed to the advancement of adsorption-based carbon capture technologies as technological strategy for the minimization of the environmental impact of the chemical industry.